PENDIDIKAN KARAKTER MULTIKULTURAL DI PONDOK PESANTREN SALAF - MAN, FAJAR (AL-QALAM: JURNAL KEPENDIDIKAN, 2023)
Multicultural education campaigns have existed in pesantren educational institutions so that it is not uncommon to find that pesantren graduates have a flexible and inclusive mindset, even some of them actually become social agents in campaigning for multicultural education, although on the other hand there are still those who are alumni of pesantren but remain exclusive, conservative, difficult to accept differences, so this will explain the process of forming multicultural attitudes in pesantren through their educational programmes. This research uses a qualitative approach. Qualitative research systematically describes the facts and characteristics of a particular phenomenon or the relationship between events and phenomena, The data collection techniques used are interviews, observation, Focus Group Discussion (FGD) and documentation. This research results in the 1st and 2nd year students tend to still have a narrow understanding, so it is still easy to blame others, this group that if they force themselves to get out of the process and stop without developing it in other institutions, then this will actually become the seeds of an exclusive group, for students from year 3 to year 8, for students who process until year 3, they are already open, because they are provided with a more open discussion forum